PENYALAHGUNAAN NARKOBA DAN PSIKOTROPIKA DI KALANGAN REMAJA - Ali Sadikin; Nur Linda (Jurnal Ushuluddin Adab dan Dakwah, 2018)
Drug can cause negative effects that will cause mental and behavioral disorders, resulting in disruption of the neuro-transmitter system in the central nervous system in the brain. Disorders of the neuro-transmitter system will lead to the interruption of cognitive (mind-nature), affective (nature, mood, or emotion), psychomotor (behavioral), and social aspects. Countermeasures of students and students who have been exposed to drugs include prevention, treatment and rehabilitation. Drugs there are various types such as: heroin, marijuana, putaw, cocaine, shabu-shabu, and alcohol included in the class of drugs. The benefits are felt only for a moment. However its impact obviously a lot. Many organs become damaged, when used drugs. Time of operation (because of an occurrence) will no longer be able to anesthetize for its users. The exact cost to be able to consume these illegal goods, is very expensive. One of them could be enter jail, if caught apparatus.